Comparison of eating disorders symptoms and body image between individidual and team sport adolescent athletes during the COVID-19 pandemic - Firoozjah, M. H.; Shahrbanian, S.; Homayouni, A.; Hower, H. (Journal of Eating Disorders, 2022)
Background: COVID-19 has significantly disrupted the routines of school sports for adolescent athletes, which can affect their usual eating behaviors and body image. Specific pressures of individual sports (e.g., strict weight requirements, revealing sports attire, aesthetic judgments), vs. team sports, may further increase the risk of eating disorders (ED) and distorted body image.